FLOATING NUCLEAR POWER PLANTS ON THE HORIZON. DO WE NEED A REVISED BRUSSELS CONVENTION ON THE LIABILITY OF THE OPERATORS OF NUCLEAR SHIPS? - Handrlica, Jakub (UI Scholars Hub, 2025)
Adopted in 1962, the Brussels Convention on the Liability of the Operators of Nuclear Ships has been considered an obsolete instrument for the last 60 years. In light of renewed interest in floating nuclear power plants (FNPPs), this article revisits the regime of this half-forgotten Convention and calls for its modernisation. The fact is that a robust legal framework for liability and compensation must accompany any prospective deployment of FNPPs. This article argues that adopting a Revised Brussels Convention will help address these challenges. This article aims to identify the reasons for this modernisation and to outline its significant features. It also argues that adopting a Revised Brussels Convention could represent an important opportunity to establish a nuclear liability framework for FNPPs in countries such as Indonesia, Sri Lanka, Thailand, or Vietnam.